PEMBUATAN DAN KARAKTERISASI MEMBRAN BERBAHAN DASAR LIMBAH STYROFOAM MENGGUNAKAN METODE ELEKTROSPINNING - Sari, Rena Juwita; Maria Ratih Puspita,; Fitria Basuki Sukandaru, (ReTII, 2019)
ABSTRACT Styrofoam is a type of organic chemical that cannot be broken down by nature. The existence of Styrofoam waste which has more and more adverse impacts on health and the environment, so it is necessary to find a solution so that its use can be minimized as well as efforts to reduce these adverse effects. One of the efforts made is to convert styrofoam waste into membranes. This study aims to synthesize and characterize the use of styrofoam waste as a membrane using the electrospinning method. 2 gram of Styrofoam was dissolved into the orange peel water of 5 ml, 10 ml, 15 ml and 20 ml. Styrofoam membranes are perfectly formed in styrofoam solution with 10 ml and 15 ml orange peel water. The FTIR spectrum results explain the shift of the -OH group to the wave number 3277.48 cm-1 with a wider peak and the ester group shifting at the wave number of 2084.49 cm-1 with a sharp absorption spectrum. Meanwhile, the results of SEM styrofoam membrane with 10 ml orange peel water and 15 ml, have a very good morphology and no beads. The average diameter of styrofoam fiber with 10 ml orange peel water is 237 Â± 26 nm and styrofoam with 15 ml orange peel water is 334 Â± 40 nm. With all the advantages of the membrane is expected to provide benefits for the environment and economically. Keywords: styrofoam, membrane, orange peel water, electrospinning